A Piezo‐Fenton System with Rapid Iron Cycling and Hydrogen Peroxide Self‐Supply Driven by Ultrasound. Issue 71 (26th October 2022) - Ge, Lin; Xiao, Jie; Liu, Wencheng; Ren, Guolan; Zhou, Chi; Liu, Junan; Zou, Ji‐Jun; Yang, Zixin
Abstract: The piezo‐Fenton system has attracted attention not only because it can enhance the Fenton reaction activity by mechanical energy input, but also because it is expected to realize a class of stimuli‐responsive advanced oxidation systems by regulating energy input and hydrogen peroxide self‐supply, thus greatly enriching the application possibilities of Fenton chemistry. In this work, a series of Fe‐doped g‐C3 N4 (g‐C3 N4 ‐Fe) as a piezo‐Fenton system were synthesized where the iron stably immobilized through Fe−N interaction. The piezo‐induced electrons generate on g‐C3 N4 matrix support the conversion of Fe(III) to Fe(II) and promote rate‐limiting step of Fenton reaction. With the optimal Fe loading, g‐C3 N4 ‐0.5Fe can achieve methylene blue (MB) degradation under ultrasonic treatment with first‐order kinetic rate constants of 75×10 −3  min −1 . Most importantly, the g‐C3 N4 ‐Fe can maintain good catalytic activity in a wide pH range (pH=2.0∼9.0) and be cyclic used without iron leaching to solution (<0.001 μg ⋅ L −1 ), overcoming the disadvantage of traditional Fe‐based Fenton catalysts that can only be applied under acidic conditions and prone to secondary pollution. In addition, g‐C3 N4 ‐0.5Fe also exhibits antibacterial properties of Escherichia coli and Staphylococcus aureus under ultrasound. Hydroxyl radicals mainly contribute to the degradation of MB and the sterilization process. Our work is an attempt to clarify the role of g‐C3 N4 ‐Fe in the conversion of mechanical energy to ROS and provide inspirations for the piezo‐Fenton system design. Abstract : A series of g‐C3 N4 ‐Fe was synthesized with varied Fe amount to construct a piezo‐Fenton system driven by ultrasound, achieving the coupling of piezoelectric processes and Fenton reactions without exogenous hydrogen peroxide. Electrons generated in the piezoelectric process takes part in hydrogen peroxide production and accelerate the Fe 2+ /Fe 3+ cycle. The piezo‐Fenton system exhibited excellent and stable hydroxyl radical generating capacity in pH 2–9 without iron leaking, and the hydroxyl radicals mainly contributed to the degradation of MB and the sterilization process.